POHON PISANG DALAM KARYA SENI GRAFIS CETAK SARING (SERIGRAPHY) - DEBY RAMADHANI THAIB, Drs. Ariusmedi, M.Sn (Universitas Negeri Padang, 2019)
The creation of this final work aims to visualize banana tree in graphic print design (serigraphy). The work displays several forms of banana trees that have a philosophy in life. The embodiment method of this final work goes through five stages: preparation, elaboration, synthesis, concept realization, and completion. Author Successfully Realizing 10 works with the title: great teacher, patience is beautiful, my purpose, generation, noble, sacrifice, offer love, life, rise, leave benefits.Keywords: Banana Tree, Graphic Art, Screen Printing